Humane relationships as a basic component of the content of forming aesthetic environment of pupils primary and high school (Pedagogy of Higher and Secondary Education, 2013)
Sierykh L. V. Humane relationships as a basic component of the content of forming aesthetic environment of pupils primary and high school.The article deals with the results of the experiment under the topic of the research. The degree of ability of pupils to the aesthetic activity and the degree of understanding of the aesthetic values of the surrounding world, the manifestation of interest in the art determined, making humanistic relationship. The essence of human relations students primary and high schools and show the impact of these relations on the formation of the aesthetic environment seniors.
Keywords: humanistic relationship; aesthetic environment; the teacher-experimenter; schoolchild and high school principals; aesthetic activity